Need Analysis on English for Specific Purposes of Marketing Major Students - Wiranda Gusti Pratami; Syamsul Rizal; Endang Haryanto (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
This study aims at determining the teaching materials needed by marketing students at SMKN 1 Kota Bengkulu and analyzing students' needs in learning English at SMKN 1 Kota Bengkulu. The subjects of this study were thirty four students of grade 10 students at SMKN 1 Kota Bengkulu. There were 34 students who participated in this research gathered by using purposive sampling The research method in this research was descriptive qualitative, and the instruments used in data collection were questionnaires, interviews and documentation. The results showed that teaching materials that have not been specific and English learning materials that are still general in nature, and ESP material have not yet available at SMKN 1 Kota Bengkulu. Second, the data indicated that the English language skill most needed by marketing students was speaking, and they claimed speaking was a useful skill to support their future work. In conclusion, this study recommends teachers at SMKN 1 Kota Bengkulu to pay more attention to the students ‘needs in learning English as solution to improve their abilities in learning English.